3D-FSE Isotropic MRI of the Lumbar Spine. Issue 4 (May 2015) - Blizzard, Daniel J.; Haims, Andrew H.; Lischuk, Andrew W.; Arunakul, Rattalerk; Hustedt, Joshua W.; Grauer, Jonathan N.
<x xml:space="preserve">Abstract</x> Study Design: Retrospective diagnostic trial. Objective: To determine the diagnostic performance of 3-dimensional isotropic fast/turbo spin-echo (3D-TSE) in routine lumbar spine magnetic resonance imaging (MRI). Summary of Background Data: Conventional 2-dimensional fast spin-echo (2D-FSE) MRI requires independent acquisition of each desired imaging plane. This is time consuming and potentially problematic in spine imaging, as the plane of interest varies along the vertical axis due to lordosis, kyphosis, or possible deformity. 3D-TSE provides the capability to acquire volumetric data sets that can be dynamically reformatted to create images in any desired plane. Methods: Eighty subjects scheduled for routine lumbar MRI were included in a retrospective trial. Each subject underwent both 3D-TSE and conventional 2D-FSE axial and sagittal MRI sequences. For each subject, the 3D-TSE and 2D-FSE sequences were separately evaluated (minimum 4 wk apart) in a randomized order and read independently by 4 reviewers. Images were evaluated using specific criteria for stenosis, herniation, and degenerative changes. Results: The intermethod reliability for the 4 reviewers was 85.3%. Modified intermethod reliability analysis, disregarding disagreements between the lowest 2 descriptors for appropriate criteria (equivalent to "none" and "mild"), revealed average overall agreement of 94.6%. Using the above, modified criteria, interobserver variability for 3D-TSE was 89.1% and 88.3% for 2D-FSE (P=0.05), and intraobserver variability for 3D-TSE was 87.2% and 82.0% for 2D-FSE (P<0.01). The intermethod agreement between 3D-TSE and 2D-FSE was statistically noninferior to intraobserver 2D-FSE variability (P<0.01). Conclusions: This systematic evaluation showed that there is a very high degree of agreement between diagnostic findings assessed on 3D-TSE and conventional 2D-FSE sequences. Overall, intermethod agreement was statistically noninferior to the intraobserver agreement between repeated 2D-FSE evaluations. Overall, this study shows that 3D-TSE performs equivalently, if not superiorly to 2D-FSE sequences. Reviewers found particular utility for the ability to manipulate image planes with the 3D-TSE if there was greater pathology or anatomic variation.